Association between Restless Legs Syndrome and Sleep Disturbance and 3-Year Mortality in Hemodialysis Patients - Lanbo Teng; Huanan Li; Yingying Han; Tao Yuan; Chuhan Xu; Tao Tan; Wenxiu Chang (Kidney Diseases)
Introduction: Whether restless legs syndrome (RLS) and sleep disturbance (SD) in hemodialysis (HD) patients influence all-cause and cardiovascular mortality remains controversial. The aim of this study was to evaluate the association between RLS or SD and 3-year mortality in HD patients. Methods: A total of 301 patients who underwent HD were examined in April 2021 and were followed up for 3 years. The median follow-up time was 36.0 [33.3, 36.0] months. Fifty-four patients fulfilled the diagnosis of RLS (17.9%), 126 patients complained of SD (41.9%). Demographic parameters, clinical features, laboratory indices, and two questionnaires to assess the diagnosis of RLS and sleep status were collected. All-cause mortality and cardiovascular mortality in this population were evaluated. Cox regression analyses and Kaplan-Meier curves were performed to determine the effect of RLS or SD on 3-year mortality. Results: The RLS group reported that 29 patients (53.8%) exhibited concurrent symptoms of SD. The presence of RLS or SD alone did not significantly elevate the risk of all-cause mortality (p = 0.053 and p = 0.193). However, the coexistence of RLS and SD was identified as an independent risk factor for all-cause mortality (p = 0.011). Furthermore, the various combinations associated with RLS or SD were found to be independently correlated with the risk of cardiovascular death (p < 0.05). Conclusion: The combination of RLS and SD in HD patients is associated with an increased risk of cardiovascular and all-cause mortality, underscoring the clinical significance of this association.